A Study Comparing Rooming-in with Separate Nursing - Syafruddin Mapata; Djauhariah A, M.; Dasril Daud (Indonesian Pediatric Society, 1988)
A study comparing rooming-in with separate nursing involving 253 and 161 pairs of mothers and their newborns respectively, was carried out in Ujung Pandang General Hospital from September 1985 to February 1987 inclusive. Breastmilk production started earlier in mothers on rooming-in program compared to those with separate nursing. Jaundice was more often seen and physiological body weight loss more obvious in the separate nursing than in the rooming-in group. This study failed to show the differences in the incidence of diarrhea and moniliasis between the two systems, but the overall morbidity of nosocomial infections seemed to be lower in the rooming-in group.